2020
DOI: 10.1021/acs.jmedchem.0c00602
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Synthesis of Methyl-β-d-galactomalonyl Phenyl Esters as Potent Galectin-8N Antagonists

Abstract: Galectin-8 is a β-galactoside-recognizing protein having an important role in the regulation of bone remodeling and cancer progression and metastasis. Methyl β-d-galactopyranoside malonyl aromatic esters have been designed to target and engage with particular amino acid residues of the galectin-8N extended carbohydrate-binding site. The chemically synthesized compounds had in vitro binding affinity toward galectin-8N in the range of 5–33 μM, as evaluated by isothermal titration calorimetry. This affinity direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“… 36 , 37 A recent study has shown that treatment of SUM159 breast cancer cells with exogenous galectin-8 stimulated the secretion of IL-6, IL-8 and IL-1β, while cotreatment with galectin-8 antagonists blocked this effect. 18 Since MDA-MB-231 cells express galectin-8 endogenously, we reasoned that inhibition of endogenous galectin-8 might reduce proinflammatory cytokine secretion in these cells. To this end, we treated MDA-MB-231 cells with compounds 6a and 1 at two different concentrations (10 and 100 μM).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 , 37 A recent study has shown that treatment of SUM159 breast cancer cells with exogenous galectin-8 stimulated the secretion of IL-6, IL-8 and IL-1β, while cotreatment with galectin-8 antagonists blocked this effect. 18 Since MDA-MB-231 cells express galectin-8 endogenously, we reasoned that inhibition of endogenous galectin-8 might reduce proinflammatory cytokine secretion in these cells. To this end, we treated MDA-MB-231 cells with compounds 6a and 1 at two different concentrations (10 and 100 μM).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Achieving selectivity for galectin-8N over the other mammalian galectins has always been a challenging task, due to the substantial similarity of different galectin CRDs and even between 8N and 8C CRDs. The previously reported synthetic galectin-8N ligands include a coumarin-galactoside derivative ( K d = 200 μM), a methyl β- d -galactomalonyl phenyl ester ( K d = 5.7 μM), a quinoline-galactoside ( K d = 1.5 μM), and a recently reported benzimidazole-galactoside 1 ( K d = 1.8 μM) (Figure ). Of particular note is a recently reported tricyclic galactose-benzene hybrid 2 ( K d = 180 μM) which has about 2-fold selectivity over galectin-1 and a high 23-fold selectivity over galectin-3 (Figure ).…”
mentioning
confidence: 99%
“…Similarly, Gal-8 direct binding at the SARS-CoV-2 coronavirus RBD, might impede viral infection. Prototypes of Gal-8 inhibitors [ 146 , 147 ] are already available. Yet, further studies are required to unravel the role of Gal-8 in tumor growth and in the immunopathogenesis of COVID-19, before considering it as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the recently described monosaccharide galactose-based antagonist of human Gal-8. This inhibitor has an affinity in the low micromolar range and is capable of inhibiting the secretion of cytokines by breast cancer cells [ 130 ].…”
Section: Approaches For Targeting and Delivery Of Galectinsmentioning
confidence: 99%